"His most ardent desire is to be ranked with Zola and rejected by Mudie": Gerard; or The World the Flesh and the Devil – M. E. Braddon's Fin-de-Siècle Faustian Rewrite. Issue 1 (2019) - Hatter, Janine
No abstract available